Analysis of inorganic and organic constituents of myrrh resin by GC-MS and ICP-MS: An emphasis on medicinal assets - Syed Rizwan Ahamad; Abdul Rahman Al-Ghadeer; Raisuddin Ali; Wajhul Qamar; Suliman Aljarboa (Elsevier, 2017)
The aim of the present investigation was to explore the constituents of the Arabian myrrh resin obtained from Commiphora myrrha. The organic and inorganic composition of the myrrh gum resin has been investigated using gas chromatography-mass spectrometry (GC-MS) and inductively coupled plasma-mass spectrometry (ICP-MS). Analysis executed by ICP-MS reveals the presence of various inorganic elements in significant amount in the myrrh resin. The elements that were found to be present in large amounts include calcium, magnesium, aluminum, phosphorus, chlorine, chromium, bromine and scandium. The important organic constituents identified in the myrrh ethanolic extract include limonene, curzerene, germacrene B, isocericenine, myrcenol, beta selinene, and spathulenol,. The present work complements other myrrh associated investigations done in the past and provides additional data for the future researches.